REFLEKSI TERHADAP HUBUNGAN LEGISLASI: DEWAN PERWAKILAN RAKYAT DAN DEWAN PERWAKILAN DAERAH - Iswan toro (Universitas Slamet Riyadi, 2018)
The journey of the Regional Representative Council (DPD) in the constitution is considered to still not compensate for the dynamics of proliferation of legislation. The reason is that the function of the DPD with the DPR in the field of legislation has been tugging and there has been intense competition in the formation of legislation, on the one hand the existence of the DPR as an institution holding a legislative function born earlier is considered to dominate the formation of legislation. On the other hand, the existence of the DPD as a new institution that is also given a legislative function, its authority is considered to be too small when compared to the authority of the DPR in the process of establishing legislation. Even the DPD is considered to add to the problem of over regulation in Indonesian legislation. Borrowing the term Richard Susskind mentions that hyper regulations or obesity are legal and over regulation. This situation led to the implementation of the DPD's legislative function not being optimal because it tends to be half-hearted. In other words, the existence of the DPD as the holder of legislative power is still under the shadow of the DPR, so it has not been taken into account in the process of establishing legislation in Indonesia, even though it has been corrected by the Constitutional Court through Decision of the Constitutional Court Number 92/PUU-X/2012 and Decision Constitutional Court Number 15/ PUU-XIII/2015, but the decision was ignored.